Odpowiedzi

2010-03-20T11:19:06+01:00
A)
3(x-40-492x-7)=2(x+5)
3x-120-1476x-21=2x+10
-120-21-10=2x-3x+1476x
-151=1475x
x=-0,102373
b)
2(2x-3)+3(4-x)=-(x=1)
4x-6+12-3x=-x-1
x+6=-x-1
2x=-6 |:2
x=-3
c)
2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
-6-12+6+2=-3x+4x-2x+4x
-10=3x
x=3,333333
d)
6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+4x
3x+12=8x-6
12+6=8x-3x
18=5x |:5
x=3,6
Najlepsza Odpowiedź!
2010-03-20T11:20:28+01:00
A) 3x - 40 - 1476x - 21 = 2x+ 10

3x-1476x-2x= 10 + 40+ 21
-1475x = 71/ :-1475

x= - 20.77464

b)2(2x-3)+3(4-x)=-(x=1)

4x - 6 + 12 - 3x= -x + 1
4x-3x+x= 1-12+6
2x=7 /:2x
x=-3.5

c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)

2x-6- 12-4x= -3x-6+4x-2
2x-4x +3x- 4x= 6-2+6+12
-3x= 22/:-3x
x= - 7,(3)

d)6(x+1)+3(2-x)=2(2x-1)-(4-x)

6x+6+6-3x= 4x-2 - 4+x
6x-3x-4x-x= -2-4-6-6
-2x=-18/ -2x
x=9

liczę na naj
pozdrawiam arek7234

1 5 1
  • Użytkownik Zadane
2010-03-20T11:22:11+01:00
B) 4x-6+12-3x=-1-x |+x
2x+6=-1 | -6
2x=-7
x=-3,5
c) 2x-6-12-4x=-3x-6+4x-2
-2x-18=-x-8 |+x
-x-18=-8 |+18
-x=10
x=10
d) 6x+6+3-3x=4x-2-4+x
3x+9=5x-6 |-3x
9 = 2x-6 |+6
15 = 2x
x=7,5